A Fuzzy Reasoning Model for Action and Change in Timed Domains. Issue 8 (8th May 2013) - Zhang, Youzhi; Luo, Xudong; Shen, Yuping
<x xml:space="preserve">Abstract</x> This paper proposes a fuzzy approach for reasoning about action and change in timed domains. In our method, actions and world states are modeled as fuzzy sets over time axis. Thus, their temporal relations and time constraints can be modeled as fuzzy rules. So, our method handles well the issue that action happens at an approximate time and then the states also change at an approximate time, which has not been solved well in the existing work. Finally, our method is used to solve the classic problem of rail‐road crossing control in a fuzzy environment. The theoretical and simulation analysis shows that the controller using our method works well.